Global treatment of haemorrhoids-A worldwide snapshot audit conducted by the International Society of University Colon and Rectal Surgeons. - ERGENÇ, MUHAMMER (My University, 2024)
Aim: There is no universally accepted treatment consensus for haemorrhoids, and thus, management has been individualized all over the world. This study was conducted to assess a global view of how surgeons manage haemorrhoids. Methods: The research panel of the International Society of University Colon and Rectal Surgeons (ISUCRS) developed a voluntary, anonymous questionnaire evaluating surgeons' experience, volume and treatment approaches to haemorrhoids. The 44 multiple-choice questionnaire was available for one month via the ISUCRS email database and the social media platforms Viber and WhatsApp. Results: The survey was completed by 1005 surgeons from 103 countries; 931 (92.6%) were in active practice, 819 (81.5%) were between 30 and 60 years of age, and 822 (81.8%) were male. Detailed patient history (92.9%), perineal inspection (91.2%), and digital rectal examination (91.1%) were the most common assessment methods. For internal haemorrhoids, 924 (91.9%) of participants graded them I–IV, with the degree of haemorrhoids being the most important factor considered to determine the treatment approach (76.3%). The most common nonprocedural/conservative treatment consisted of increased daily fibre intake (86.9%), increased water intake (82.7%), and normalization of bowel habits/toilet training (74.4%). Conservative treatment was the first-line treatment for symptomatic first (92.5%), second (72.4%) and third (47.3%) degree haemorrhoids; however, surgery was the first-line treatment for symptomatic fourth degree haemorrhoids (77.6%). Rubber band ligation was the second-line treatment in first (50.7%) and second (47.2%) degree haemorrhoids, whereas surgery was the second-line treatment in third (82.9%) and fourth (16.7%) degree symptomatic haemorrhoids. Rubber band ligation was performed in the office by 645(64.2%) of the participants. The most common surgical procedure performed for haemorrhoids was an excisional haemorrhoidectomy for both internal (87.1%) and external (89.7%) haemorrhoids – with 716 (71.2%) of participants removing 1, 2 or 3 sectors as necessary. Conclusion: Although there is no global haemorrhoidal treatment consensus, there are many practice similarities among the different cultures, resources, volume and experience of surgeons around the world. With additional studies, a consensus statement could potentially be developed. KEYWORDS: haemorrhoids, survey, treatment of haemorrhoids
Keywords: haemorrhoids; survey; treatment of haemorrhoids